Cassida sekerkai sp. nov. (Coleoptera: Chrysomelidae: Cassidinae), a new species from Madagascar - Borowiec, Lech; Świętojańska, Jolanta (Zootaxa, 2017)
Cassida sekerkai sp. nov. is described from Madagascar. This species belongs to the group with completely black pronotal and elytral disc.